Numerical analysis of direct contact condensation-induced water hammering effect using OpenFOAM in realistic steam pipes - Pham, T.Q.D.; Choi, Sanghun (International journal of heat and mass transfer, 2021)
•Temperature/pressure variations in steam pipes are studied using OpenFOAM v.6.•Numerical simulations are performed on steam pipes used in PMK-2 and KEPCO.•The CFD codes are validated with 1D Stefan condensation and evaporation problems.•Simulation results are also compared with experimental ones previously published.•High flow rates, i.e., large Froude number, reduces pressure peaks in steam pipes. Direct contact condensation (DCC)-induced water hammer in a horizontal pipe is an important phenomenon observed in many industrial fields such as nuclear and thermal engineering. This study aims to simulate the DCC-induced water hammering effect in previously designed steam pipes. The numerical simulation for the water hammering was performed in our computational fluid dynamics (CFD) solver modified from interFoam included in the open-source software OpenFOAM v.6. The new solver includes an energy equation and existing phase change models. Computational domains were reconstructed using our Python-based semiautomated mesh-generation algorithm to investigate local variations of temperature and pressure inside a steam pipe. Continuity, momentum, and energy equations of a volume of fluid model were discretized using the pressure-implicit method for the pressure-linked equation algorithm. Implicit Euler and central difference schemes were used for temporal and spatial discretization, respectively. The CFD solver with the phase change model was validated using a one-dimensional Stefan problem's benchmark case. In a PMK-2 steam pipe, the temperature drop due to the water hammering was temporally consistent with the existing experimental result. A smaller pressure was captured in the region where the phase change of steam to water was observed. This induced an adverse pressure gradient that drove the water moving backward, resulting in water hammering. The water hammering was further investigated by changing the water temperature and flow rate in a different steam pipe. A higher water flow rate (i.e., large Froude number) was found to dampen the steam pipe's pressure shock.